Research on Rotor Dynamic Characteristics of High Speed Aviation Piston Pump - Lijun Chen; Rushen Deng; Jun Zha; Jianning Gu; Tianxiang Xia; Runlin Chen (Lubricants)
The high-speed aviation piston pump plays a vital role in hydraulic systems in the aviation field. Extremely complex force situations happen during running operations due to the coupling between multiple components, as a result of the overall dynamic characteristics being complex and changeable, which brings great difficulties and challenges to its performance optimization. Taking the high-speed aviation piston pump as the research object, a mechanical balance equation of the piston based on the dynamic balance method was proposed. The reaction force of the swashplate and the influence of rotational speed and outlet pressure on it were modeled. Through the balance of the system and the component subsystem, the load of the support bearing of the piston pump under different working conditions is analyzed, as well as the influence of the rotational speed and the outlet pressure on the bearing stiffness by the quasi-static method. In addition, the discrete model of the piston pump spindle and the discrete model of the rotor system are established. The accuracy of the model is verified by the finite element method. The maximum error of the spindle discrete model is 6.13%, and the maximum error of the rotor system discrete model is 15.28%. The transfer matrix analysis shows that the working condition parameters have little effect on the critical speed of the spindle and rotor system, and the outlet pressure has a more significant effect than the speed. The research results provide a theoretical basis and analysis method for the dynamic analysis and structural optimization of the high-speed aviation piston pump.